8 Does point-of-care simulation improve the care of deteriorating patients on medical and surgical assessment units?. (17th November 2016) - Forster, Michael; King, S; Ward, C; Chopra, M; Sice, P; Mason, T
Abstract : Introduction: Point-of-care simulation is an increasingly used technique to train multi-disciplinary teams in Human Factors, ergonomics and establish reasons for barriers to safer patient care. We investigate if this method could be used to improve care of deteriorating patients. Methods: A one-year Health Education England fellowship funded two simulation fellows from nursing and medical backgrounds. An intervention utilising simulation and targeted teaching sessions was performed on assessment units of a university hospital. The sessions included a sepsis micro-teach, medium fidelity simulation and debrief, with discussion of human factors. The primary outcome measure audited was percentage of triggers detected and escalated at baseline, six months and regularly throughout the last six months. Secondary outcome measure was percentage of septic patients, as defined by sepsis guidelines, who had documentation and administration of the 'Sepsis 6' bundle. Feedback on the training was also collated. Results: approximately 300 educational hours were delivered to 105 doctors, nurses and health care assistants. forty-three sessions were planned, but only 25 (58%) proceeded due to hospital-wide operational pressures. Increased cancellations occurred over winter, which correlated with a decrease in escalation rates. Detection and escalation of yellow triggers increased from 23% to 88%, with amber triggers from 18% to 100% on the medical assessment unit. Delivery of the sepsis bundle was variable and not statistically significant. Feedback was positive with over 90% stating they would like more training and would recommend it to their colleagues. Although success with trigger escalation could not be wholly attributed to the simulation training, there was a Statistical difference and no other interventions took place during the training period. Conclusion: We suggest that point-of-care simulation improves awareness of deteriorating patients when delivered to an inter-professional team. Training difficulties relate to staff release and operational pressures.